Optimal network configuration in liner shipping : it's challenges - Muhammed Khairul Aziz (2008)
In the container shipping industry one thing is certain: the race to acquire the capabilities customers demand-namely shorter transit time for reduced costs-will intensify. Carriers have to realize that the optimal network design is not only function of carrier-specific operational factors.